Perfectionism and resilience in Venezuelan adults - Aguilar Durán, Leonardo Andrés (2025)
The present research aimed to examine whether perfectionism and some demographic variables can predict levels of resilience (and their dimensions) in adults from Venezuela. The design was cross-sectional predictive, through logistic regression analysis. Participants were 313 Venezuelan mature adults (M = 46.44 years), mostly women (82.7%), residents of the interior of the country (70.9%), with higher education (64.2%), and paid employment (67.9%). An adapted version of the Multidimensional Perfectionism Scale (Frost et al., 1990) and the Resilience Scale for Adults (Hernández y Lezama, 2016) was applied via Google Forms. Organization was a positive predictor of resilience and two of its dimensions (OR = 1.13 - 1.27), while fear of mistakes was a negative predictor of resilience and “morality and values” (OR = 0.96). Personal standards positively predicted“perseverance and hope” (OR = 1.12), and negatively “morality and values” (OR = 0.90). Age was the only demographic variable that predicted resilience (OR = 1.03 - 1.06). Based on these findings, the complex role of perfectionism in predicting resilience is highlighted, certain clinical implications are discussed, and some recommendations are put forward.